Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, dan Lain-Lain Pendapatan Daerah yang Sah pada Belanja Daerah - Arni Asari, Ni Made; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2018)
The purpose of this study is to determine the effect of local revenue, balance funds and other legitimate local revenue on regional expenditure. This research was conducted in Badung Regency Government. Determination of the sample using purposive sampling technique through certain criteria so that obtained sample of 60 samples. The analysis technique used in this research is multiple linear regression and hypothesis test using t-statistic to test partial regression coefficient and f-statistic to test the feasibility of research model with significance level 5%. In addition, the classical assumption test included normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The results of the analysis show that local revenues, equity funds and other legitimate local revenue simultaneously have a positive effect on local spending. local revenue, balance funds and other income. Keywords: Rregional expenditure, local revenue, balancing fund